Indices of lactate threshold and their relationship with 10-km running velocity - Nicholson, R. M.; Sleivert, G. G. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The object of this study was to determine the relationship of three measures of running velocity at lactate threshold (LT) with 10-km running velocity. The methods used to determine LT velocity (m.s-1) during submaximal treadmill running were: 1) LT1, the velocity preceding two consecutive increases in blood lactate >/= 1 mmol.L-1; 2) LTD, the velocity associated with the maximum perpendicular distance between the nonlinear regression line and the straight line formed by the two end data points of the blood lactate profile; and 3) LT4, the velocity corresponding to a blood lactate concentration of 4 mmol.L-1. Methods: Thirty competitive and recreational runners (11 female and 19 male) undertook two 10-km time trials (7 d apart), three treadmill familiarization sessions over the following 21 d, and then completed an incremental submaximal treadmill run. From blood lactate samples taken during the submaximal run, mean LT velocity (+/- SD) at LT1 (3.76 +/- 0.57), LTD (3.79 +/- 0.58), and LT4 (4.11 +/- 0.64) was determined. Pearson product moment correlation analysis revealed a strong relationship between all mean LT speeds and mean 10-km running velocity (3.77 +/- 0.57), with the strongest relationship observed for LTD (r = 0.86, P < 0.001). Correlations by gender between LTD and 10-km velocity were r = 0.84 (female) and r = 0.78 (male). Male subjects had significantly higher LT velocities than female subjects using all methods (P < 0.001), and velocity at LT4 was significantly faster than 10-km velocity and velocity at LT1 and LTD (P < 0.001). Conclusion: Of the methods measured, LTD appears to be the most sensitive and valid measure of LT velocity and may be of benefit in monitoring the training program of 10-km distance runners.